Dedifferentiated chordoma: A rare tumor with diagnostic challenge - Kalita, Dipti; Rastogi, Ruchi (Indian Journal of Case Reports, 2024)
Chordomas are rare locally invasive malignant bone tumors arising from remnants of embryonic notochord. Dedifferentiated chordoma (DC), a rare subtype, is characterized by the presence of a sarcomatous component in conventional chordoma (CC) which may arise de novo or as a malignant transformation of previously treated chordoma. The presence of dedifferentiation warrants a poor prognosis due to distant metastasis and recurrences. De novo DCs pose a diagnostic challenge especially in small biopsies and at metastatic sites. Here, we report the case of a 45-year-old female presenting with a long history of backache and constipation, finally diagnosed as DC. Radiological as well as histomorphological pictures of the tumor posed diagnostic challenges because they can mimic other tumors occurring in a similar location. We found this case worth reporting as de novo DC is rarely reported in the literature and it has the potential to pose diagnostic as well as therapeutic challenges. Here we report a case of dedifferentiated chordoma presenting with diagnostic challenge both radiologically and histomorphologically and discuss the role of immunohistochemistry.